Intergenerational Leadership: A Leadership Style Proposal for Managing Diversity and New Technologies - Virginia Ramírez-Herrero; Marta Ortiz-de-Urbina-Criado; José-Amelio Medina-Merodio (Systems, 2024)
Artificial intelligence, augmented, virtual, and mixed reality applications are improving business tools to increase their efficiency and ability to innovate. Technological innovation offers creative opportunities, but each generation values these advances differently. This study analysed the intergenerational differences and their leadership styles. The research questions are as follows: what are the main characteristics of each generation? And what leadership style is most appropriate for managing generational diversity in companies? Firstly, the main characteristics of each generation—Boomers, Generation X, Millennials, Generation Z, and Generation Alpha—were identified. Secondly, the most representative leadership styles of each generation were analysed. And thirdly, a proposal for a leadership style that can be used to better manage the intergenerational needs and technological demands of companies was presented. The development of leadership styles that take account of all generations can support economic growth and the creation of innovative and sustainable industries, as well as improve social welfare.